The feminist agenda in poltergeist : subverting synchronized dialogue. - Lee, Hsien Jun. (2012)
Classical Hollywood cinema has always been about creating the impression of realism, thereby enforcing the inseparable linkage between the visual body and its voice (which has to contain dialogue). Moreover, classical Hollywood cinema’s phallocentric nature means that it privileges the phallus as the “speaking subject… equivalent to [an] unseen enunciator” which predicates the exclusion of female voice based on “an incapacity for looking, speaking, or listening authoritatively, on the one hand, and with what might be called a ‘receptivity’ to the male gaze and voice, on the other” (Silverman 31). In other words, the female voice has to exist as pathology in order for the male voice to be dominant. By relegating the female voice to always requiring a matching female body in the filmic diegesis, classical Hollywood cinema ‘normalizes’ its females so that the males can be superior. Indeed, Michael Grant in his essay “‘Ultimate Formlessness’: Cinema, Horror, and the Limits of Meaning” informs us of Greed’s argument that “the central work of the horror film is the construction of the maternal figure as abject,” and that ultimately “all that is of the Other, is separated out and subordinated to the paternal law” (179) which objectifies females under its phallocentric gaze. In contrast to this trend, I aim to study how the female is glorified and empowered in horror films like Poltergeist (1982) via techniques that subvert synchronized dialogue, thereby allowing my readers to have a broader understanding of how the body-voice boundary in classical Hollywood cinema that pathologizes the female can be destabilized.